A Case of Uncommon Hematemesis from Acute Esophageal Necrosis - Gashi, Zaim; Maloku, Kushtrim; Hamza, Valon (IIUM Medical Journal Malaysia, 2026)
Acute esophageal necrosis (AEN) is a rare and severe condition characterized by extensive tissue necrosis of the esophagus. This condition predominantly affects the distal part of the esophagus. Reports estimate the prevalence of AEN to be up to 0.2% in autopsy studies, while endoscopic series report a prevalence ranging from 0.01% to 0.28% of cases. It primarily affects patients with poor nutritional health and multiple comorbidities often as a result of underlying systemic condition. Patients present with upper gastrointestinal bleeding, such a hematemesis and melena. We report a case of AEN in a female patient who had presented with hematemesis.